Middle Class Community Religious Moderation in Buntet Village, Astanajapura District, Cirebon Regency - Rahman Hakim, Arif (Green Publisher Indonesia, 2020)
This study focuses on religious moderation and the religious views of the middle class community in Buntet Village, Astanajapura District, Cirebon Regency. The purpose of this research is to find out how the community's religious condition and how religious views are, as well as their relation to nationality. The methodology used in this study used a qualitative descriptive analysis using in-depth interview techniques, document review, observation, and holding focus group discussions. The results found in this study indicate that religious moderation for the Muslim middle class in Buntet Village, Astanajapura District, Cirebon Regency is quite good. In this village, there are no members of the community who are anti-NKRI, anti-Pancasila, and anti-UUD 1945. As well as the diversity of the Muslim community in the Buntet area is classified as moderate, because of their religious understanding as developed by NU and Muhammadiyah